Deviations of the Surface Brightness Distribution in Isolated Elliptical Galaxies - Omar Salih (مجلة التربية والعلم, 2012)
In this paper, we present the surface brightness profiles of 48 isolated elliptical galaxies. we have adopted the r1/n – law to the observed surface brightness profiles of the adopted sample of isolated elliptical galaxies for the intermediate radial range . From best fitting profile. The results showed that the deviations are similar to previous studies, and the deviations do not  depend  on the  surrounding  environment of the galaxies, whether that were an isolated or not. Such results might be very useful to understand the structure and evolution of elliptical galaxies.